EVALUASI PEMBELAJARAN EKONOMI PADA KURIKULUM 2013 DI SEKOLAH DASAR NEGERI 03 SUMBERSARI KOTA MALANG - Irawan, Hendra; Juani, Muhamad (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2020)
The quality of a learning can be measured from the level of achievement of learning objectives. economic education is one of the learning programs that must receive full attention in terms of quality, so that it remains actualized as a learning unit that gives meaning to economic sciences for students in providing economic behavior that is rational, moral and alturistic. This study aimed to evaluate the extent of the quality of economic learning in elementary schools in SDN 03 Sumbersari, Malang. This study used a qualitative evaluation-research approach with the CIPP model, including: evaluating the aspects of context, input, process and product / output. The results showed that in the curriculum of  2013, The position of economic education was still integrated with Social Sciences (IPS) and thematically learned. the lack of space for economic subjects has an indirect effect on the decline in the enthusiasm of teachers to innovate in learning activities and in evaluating learning outcomes. Weaknesses of the aspects of educational input make the aspects of the process not carried out adequately and ultimately also have an impact on low economic learning outcomes for students